Heroic nurses. - McKown, Robin (New York Putnam, 1966)
Brief biographies of twelve great nurses including Florence Nightingale, Clara Barton, Elizabeth Kenny, and Princess Tsahai Haile Selassie.
Bibliography: p. 311-313.
Keywords: Nurses -- Biography -- Juvenile literature; Nurses